Comparison of methods to assess the integrity and separation efficiency of ultrafiltration membranes in wastewater reclamation processes. (August 2019) - Krahnstöver, Therese; Hochstrat, Rita; Wintgens, Thomas
Graphical abstract: Highlights: A variety of integrity testing methods was studied on an ultrafiltration unit. Permeate quality depends on membrane integrity, clogging and biological regrowth. Pressure decay testing detects integrity losses due to physical damaging reliably. Nanoparticle counting allows for sensitive online-monitoring of permeate quality. Flow cytometry reveals that the permeate quality is affected by bacterial regrowth. Abstract: Membrane filtration is used in many water reuse applications, thanks to its high separation efficiency with regard to particles, bacteria, cysts and in the case of ultrafiltration even viruses. However, the separation performance of a membrane system can be affected and the permeate quality can be reduced or increased by phenomena such as membrane damage, membrane fouling or microbiological regrowth on both permeate and retentate side of the membrane. Thus, in order to guarantee a sufficiently high permeate quality, the separation efficiency of a membrane system has to be assessed sensitively, reliably and, if possible, continuously. In the here presented study, a variety of different analytical methods was tested to assess the separation efficiency of ultrafiltration membranes in a pilot-scale wastewater reclamation system. After intentionally damaging the membrane to different degrees, its integrity was monitored by pressure decay testing and permeate turbidity measurements, and by continuously monitoring the concentration of micro- and nanoparticles in the permeate stream. The microbiological permeate quality was not only assessed by plate counting, but also by flow cytometric measurements. The results showed that the membrane integrity is primarily affected by physical damaging, as detectable by pressure decay testing, while the permeate quality strongly depends on particle-membrane interactions such as formation of a fouling layer or clogging of membrane defects. Nanoparticle counting was found to be a very sensitive method to continuously monitor the membrane's separation efficiency. Additionally, flow cytometry revealed that bacterial regrowth on the permeate side can affect the microbiological permeate quality in particular.